Characteristics of pinewood dust combined with vinyl ester composites through material testing and machining - Suhami, Muhammad Wafiuddin; Ab Wahab, Norfariza; Boejang, Hambali; Hamzah, Khairum; Sasahara, Hiroyuki (Jan Evangelista Purkyne University, 2022)
Natural fibre reinforced polymer (NFRP) composites can be environmentally friendly and cost-effective alternatives to synthetic fibre-reinforced composites. Major industries have expressed significant interest in the advancement of new natural fibre-reinforced composite materials. However, these materials perform poorly on their own and require further analysis since accessible information is lacking in the literature. This paper presents the results of previously reported works on natural fibre reinforced polymer composites, with strong attention to the types of fibres employed, the polymers used in the matrix, the treatment of fibres as well as the test parameters. The best proportion of composites is consequently selected. Composite materials are tested using a CNC router machine. Pinewood dust is combined with vinyl ester resin. A hand layup technique is used to prepare the samples. The availability of relevant pinewood dust and the volume of pinewood dust to be used are first determined to continue with the experiment. According to the findings, the impact of machining performance is successfully evaluated by employing the tensile strength test, Charpy V-notch impact test, flexural strength test and surface roughness measurement. The findings are derived from the microscopic assessment of the surface roughness of pinewood dust (PWD) fibre reinforced vinyl ester resin.